2020
DOI: 10.3892/etm.2020.8432
|View full text |Cite
|
Sign up to set email alerts
|

Function and mechanisms of microRNA‑20a in colorectal cancer (Review)

Abstract: Colorectal cancer (CRC) is the third most common malignancy and the second leading cause of cancer-associated mortality worldwide. CRC currently has no specific biomarkers to promote its diagnosis and treatment and the underlying mechanisms regulating its pathogenesis have not yet been determined. MicroRNAs (miRs) are small, non-coding RNAs that exhibit regulatory functions and have been demonstrated to serve a crucial role in the post-transcriptional regulatory processes of gene expression that is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 137 publications
0
19
0
Order By: Relevance
“… 17 MiRNAs play cancer-inhibiting or cancer-promoting actions to regulate the oncogenicity of CRC and are implicated in the modulation of multiple tumor cell behaviors. 18 , 19 LncRNAs have miRNA binding sites and can function as competing endogenous RNAs (ceRNAs) by sponging miRNAs, thus modulating the expression of miRNA targets. 20 Therefore, an in-depth investigation of cancer-associated lncRNAs and miRNAs in CRC may provide useful information for identifying potential targets for cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“… 17 MiRNAs play cancer-inhibiting or cancer-promoting actions to regulate the oncogenicity of CRC and are implicated in the modulation of multiple tumor cell behaviors. 18 , 19 LncRNAs have miRNA binding sites and can function as competing endogenous RNAs (ceRNAs) by sponging miRNAs, thus modulating the expression of miRNA targets. 20 Therefore, an in-depth investigation of cancer-associated lncRNAs and miRNAs in CRC may provide useful information for identifying potential targets for cancer diagnosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One of the interesting points is the anti-tumor activity of propofol as an anesthetic agent. This compound is exclusively applied in cancer therapy, and it is capable of regulating different molecular pathways in cancer therapy, particularly miRNAs [ 320 , 321 , 322 ]. In non-small cell lung cancer, propofol downregulates miRNA-21 expression to induce apoptosis in a time- and dose-dependent manner.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%
“…miRNAs are generally non-coding consist 19-22 nucleotide endogenous RNA molecules which is negatively regulates the target genes expression through cleaving mRNA and translational suppression [6]. Many evidences reported that miRNA play an important role in many biological process are cell proliferation, angiogenesis, invasion, apoptosis and organ development in different types of cancer [7,8] and, are closely associated with development cell chemoresistance in cancer cells especially in colorectal cancer [9][10][11][12][13]. In this study, we performed identi cation the aberrant expression of different miRNA in the parental and Oxaliplatin-resistant CRC using microarray analysis.…”
Section: Introductionmentioning
confidence: 99%